Multifunctional DNA hydrogels with light-triggered gas-therapy and controlled G-Exos release for infected wound healing - Yuyun Ye; Yan Liu; Shengchao Ma; Xipeng Li; Wei Wang; Xu Chen; Judun Zheng; Zhijin Fan; Yideng Jiang; Yuhui Liao (Bioactive Materials)
Infectious wound healing remains a significant medical challenge due to chronic inflammation and bacterial colonization. Effective antimicrobial and anti-inflammatory therapies are essential to facilitate wound recovery. Herein, we introduce a highly biocompatible, ROS-responsive DNA hydrogel (LGAH), modified with aggregation-induced emission luminogens (AIEgen) and incorporating ginseng-derived exosomes (G-Exos) and nitric oxide (NO) donor-L-arginine (L-Arg) to promote healing of infected wounds. The hydrogel degrades in response to elevated ROS levels, releasing therapeutic agents. Upon laser irradiation, AIEgen generates 1O2, which activates L-Arg to produce NO, leading to a synergistic antimicrobial effect. NO is particularly effective at inhibiting bacterial growth and promoting angiogenesis, supporting wound healing. G-Exos modulate immune responses, reduce inflammation, and promote the transition from the inflammatory to the proliferative phase. They also enhance cell proliferation, migration, and collagen production, which are key to tissue regeneration. In vivo experiments demonstrated that LGAH significantly accelerates S. aureus-infected wound healing by modulating the wound microenvironment and promoting tissue regeneration. Transcriptomic analysis revealed that LGAH down-regulates gene expression in inflammation and immune response signaling pathways while up-regulating genes related to energy metabolism. Biosafety evaluations at cellular and animal levels have demonstrated that LGAH possesses excellent biocompatibility and biodegradability, making it ideal for tissue repair and regeneration. This multifunctional DNA hydrogel system offers a safe and promising strategy for the clinical treatment of infected wounds.